ITRAQ based proteomic profile analysis for goat Longissimus thoracis under repeated freeze-thaw treatments. (December 2020) - Gu, Minghui; Wei, Yanchao; Zhang, Dequan; Liu, Yongfeng
Abstract: This study was designed to investigate differences in the proteomes of goat Longissimus thoracis during freeze-thaw processing using iTRAQ technology. The effects of repeated freeze-thaw cycles (1 and 2) on the color and total amino acids of goat Longissimus thoracis were clarified. In total, 159 differentially expressed proteins (DEPs) were identified in goat meat during freeze-thaw processing. The treatment of repeated freeze-thaw cycles was confirmed to affect protein digestion and fat decomposition in goat meat. DEP quality analysis identified the elongation factor 1-gamma (EF-1γ), cAMP-dependent protein kinase catalytic subunit alpha (PKA C-alpha), 40S ribosomal protein S12 (RPS12), and the collagen alpha-2(IV) chain (COL4A2) as potential proteins for reflecting the degree of meat freeze-thaw, whereas myosin regulatory light chain 2 (MYLPF), myosin light chain 1/3 (MYL1/3), and isocitrate dehydrogenase [NAD] subunit beta (IDH3B) were considered to be biomarkers for meat color. Graphical abstract: Image 1 Highlights: Novel proteome analysis of goat meat during freeze-thaw processing. Bioinformatics showed freeze-thaw affects protein digestion and fat decomposition. Four proteins were identified to reflect the degree of meat freeze-thaw. Three proteins were confirmed to be biomarkers for meat color.